Geusun Ulun Museum as Sumedang Larang Kingdom Assets Entry Points of Tourism Destinations in Sumedang - NURBAETI, Nurbaeti; RATNANINGTYAS, Heny; PANTJA DJATI, Sundring (Journal of Environmental Management and Tourism, 2024)
Visit to the Geusun Ulun Museum are still very low compared to other tourist attractions in West Java; a management strategy for the Geusan Ulun Museum is needed. This study aims to apply a SWOT analysis to the Prabu Geusan Ulun Palace as an entry point for Sumedang tourist destinations. The research was conducted by observation and interviews. The results showed that the Geusun Ulun Museum had the highest score of 3.82 in quadrant/position I, which means that the condition of the Geusun Ulun Museum is very profitable and has opportunities and strengths so that it can take advantage of current opportunities; the strategy used is the SO/Strenght Opportunity strategy including: (1) Improving the presentation of collections to be more informative and conceptual; (2) The Nazir Prince Wakaf Sumedang Foundation, the manager of the Geusun Ulun Museum, is actively promoting and developing the Royal Sunda Museum; (3) The strategic location of the Museum is the main attraction for tourists; (4) The remaining land area is still widely used for facilities and infrastructure that still need to be created; (5) Cooperating with the private sector to promote through the internet about the Geusun Ulun Museum; (6) Package and synergize tour packages with travel agents.